Arithmetic Aptitude :: Logarithm

7. If log(base 10) 5 + log(base 10)(5x + 1) = log(base 10)(x + 5) + 1, then x is equal to:

Answer: Option B

Explanation :

Given log(base 10) 5 + log(base 10)(5x + 1) = log(base 10)(x + 5) + 1
=> log(base 10) 5 + log(base 10)(5x + 1) = log(base 10)(x + 5) + log(base 10) 10
Hint: log (base Z)Z = 1
=> log(base 10)[5 (5x + 1)] = log(base 10) [10(x + 5)] ------ (Point to Remember.)
=> 5(5x + 1) = 10(x + 5)
=> 5x + 1 = 2x + 10
=> x = 3

Asked In :: Infosys

Post Your Answer Here:     

No Discussion on this question yet!